2021
DOI: 10.1177/16878140211001239
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of aerodynamic noise performance of improved air distributor for ships

Abstract: In ships, aerodynamic noise from the variable-air-volume fan is a common problem. This study experimentally explores the strategy of reshaping the traditional C-shaped channel structure to an L-shape to reduce noise. The noise level and resistance coefficient of the improved air distributor are analysed, and the results show that the noise of the original air distributor is 56.3 dB(A) under the rated working conditions (static pressure of 800 Pa and flow rate of 350 m3/h), which exceeds the International Marit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…8,9 Second, the sense of pleasure is also affected by the type and level of noise, which is determined by the pulsating parameters of the flow field. Similarly, noise reduction optimization [10][11][12] of typical components such as AD and sudden expansion and contraction was carried out by theoretical, experimental or numerical simulation methods, 13,14 which greatly reduced the sound pressure and proved the synergistic relationship between the pressure field and the sound field. 15 Several studies have demonstrated that the perforated plate can be used to reduce the turbulence intensity and achieve the control and noise elimination of the broadband noise of the pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Second, the sense of pleasure is also affected by the type and level of noise, which is determined by the pulsating parameters of the flow field. Similarly, noise reduction optimization [10][11][12] of typical components such as AD and sudden expansion and contraction was carried out by theoretical, experimental or numerical simulation methods, 13,14 which greatly reduced the sound pressure and proved the synergistic relationship between the pressure field and the sound field. 15 Several studies have demonstrated that the perforated plate can be used to reduce the turbulence intensity and achieve the control and noise elimination of the broadband noise of the pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Guo Y et.al experimentally explored the strategy of reshaping the traditional C-shaped channel structure to an L-shape, to reduce noise. The noise level and resistance coefficient of the improved air distributor were analyzed [12]. Ran et al studied the resistance coefficient of the air conditioning pipeline at the elbow joint.…”
Section: Introductionmentioning
confidence: 99%